Method for Determining Accurate Initial Air Pressure Range of Air Suspension Airbag Based on Vehicle Ride Comfort Simulation Analysis. Issue 1 (May 2019) - Zhou, Quan; Yuan, Puguang; Tudor, Tim; Wang, Xudong; Guo, Zhangwei; Huang, Yihui; Sun, Jingfeng; Wang, Boyun
Abstract: With the rapid development of automobile technology and the improvement of people's quality of life, people put forward higher requirements for vehicle ride comfort. Shock absorption has become an important direction for automobile research, manufacturing and optimization. The traditional air suspension airbag delimits the initial air pressure range based on the bearing capacity of the airbag material, so the range of the pressure is inaccurate. Considering optimizing ride comfort of the vehicle, this paper proposes a method to determine the accurate initial air pressure range. In order to determine the accurate initial air pressure range of the airbag, this paper needs to know the vehicle ride comfort under any air pressure. The airbag spring stiffness is calculated using the airbag model in MATLAB environment. A shock absorber with appropriate damping coefficient is selected by using the single mass system model and the airbag spring stiffness. Suspension stiffness is calculated by constructing a single wishbone beam independent suspension model and using the airbag spring stiffness. The damping coefficient and suspension stiffness are introduced into the Simulink five-degree-freedom vehicle model to obtain the acceleration signals of every part including the seat whose RMS value of the acceleration signal is used to judge the ride comfort of the vehicle. Under the specific simulation conditions in this paper, there is an accurate range (14∼16kPa) in the rough range (12∼20kPa) of the initial air pressure of the airbag to make the vehicle ride smoothly.